Wagnerian Singing and the Limits of Vocal Pedagogy - Parr, Sean (Current Musicology, 2020)
This article explores how singing became “Wagnerian” after Wagner’s death in 1883. Common perceptions of Wagnerian singing center on its sheer volume, its muscular and heroic tone. Interestingly, the last century of Wagnerian singing has been shaped by a school of singing defined not by theories of resonance and phonation, but by the disciplining of the breathing body. In arguing that certain ideas of singing technique adapted to and then defined this Wagnerian ideal, the essay demonstrates that the “work” of the operatic singer involves much more than having “a voice.” In doing so, the article opens up a new space for considering Wagnerian singing, a topic neglected in scholarly literature. More generally, it also builds on recent scholarship that has begun to explore the voice in all its material realities and pedagogy as a crucial site of the construction of sonic ideals.